Comparative Study between Topographic and Anatomical Motor Branch Localization of the Ulnar Nerve during Supercharged Ulnar Nerve Repair by Anterior Interosseous Nerve Transfer - Abdalraheem, Yasser Ahmed; Nazim, Wael Mohamed; Samy Ahmed, Mostafa Mahmoud; Ahmed Hassanein, Mostafa Mahmoud; Hewedy, Mohamed Ahmed (Journal of Neonatal Surgery, 2025)
Background: The research aims to determine if anatomical localization is more effective than topographic localization in supercharged nerve repair for claw hand deformity correction & intrinsic muscle power recovery. Methods: We performed comparative randomized prospective research on 26 cases with ulnar nerve injury who presented to Beni-Suef University Hospitals and Cairo University Hospitals in the period from March 2021 to March 2024. Thirteen patients were managed with ulnar nerve repair+ supercharged end-to-side nerve transfer (UR+SETS), where a motor branch of the nerve is anatomically localized, and 13 cases have been treated by UR+SETS, where a motor branch of the ulnar nerve has topographically been localized. Results: The age group of topographic localization consisted of 33.23± 10.07 years, with the majority of the participants being male (76.9%). Additionally, the anatomical localization group’s mean age was 37.92± 7.66 years, with the majority of the participants being male (69.2%). The two groups did not exhibit any statistically significant variances in terms of gender or age (p above 0.05). We observed very good to excellent outcomes in both groups according to the recovery of reduction of deformity & intrinsic muscle function, as evidenced by the earlier enhancement in the score of Raji &Birch & Brand’s principles. Conclusion: A study found no significant variance in motor & functional outcomes among the 2 groups regarding the localization of the ulnar nerve motor branch, suggesting that prioritizing this location is crucial for restoring nerve function in severe cases.